An atrocity archive: sensory expression of past-present-future. Issue 2 (3rd July 2021) - Thorne, Benjamin
ABSTRACT : The violence and related crimes committed during the genocide against the Tutsi, April-July 1994, led to the creation of the International Criminal Tribunal for Rwanda. This international machinery of justice was located in the neighbouring country of Tanzania. The often complex, draining, meandering, problem-prone legal proceedings, sprawling across 21 years generated a rich and diverse archive containing fragments of pre-genocide, genocide and post-genocide periods. This somewhat side-lined archive is an interplay between plural experiences, memory, dialogue, power, and users. Atrocity archives and their material are sites of stimulation. They stimulate memory, dialogue, and the senses. The senses accompany all those who adventure with archive material. Accompany in both obvious and more subtle ways, which nonetheless can be profound. The stimulation of visual material is compelling, although sound, taste, touch, smell can equally weave, entwine and manifest during archival encounters.